2012
DOI: 10.1002/pon.3218
|View full text |Cite
|
Sign up to set email alerts
|

Social support and quality of life among lung cancer patients: a systematic review

Abstract: Objective: This systematic review analyzed the relationships between social support and quality of life (QOL) indicators among lung cancer patients. In particular, the patterns of relationships between different social support facets and sources (received and perceived support from healthcare professionals, family, and friends) and QOL aspects (emotional, physical symptoms, functional, and social) as well as the global QOL index were investigated.Methods: The review yielded 14 original studies (57% applying cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
3
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 53 publications
4
89
3
12
Order By: Relevance
“…Better QOL among patients with advanced NSCLC under chemotherapy has been consistently associated with younger age (Henoch, Bergman, Gustafsson, Gaston-Johansson, & Danielson, 2007;Liu et al, 2009); better economic status (Liu et al, 2009;Pan, Xu, Wang, & Zhu, 2011); being employed (Hermann & Looney, 2011); stronger social support (Liang, Jiang, & Li, 2007;Luszczynska, Pawlowska, Cieslak, Knoll, & Scholz, 2013); better performance status (Henoch et al, 2007;Hermann & Looney, 2011;Iyer, Taylor-Stokes, & Roughley, 2013); better treatment response to chemotherapy (Liu et al, 2009;Zhan, 2008); less frequent, severe, and distressing physical symptoms (Hermann & Looney, 2011); and less anxiety and depressive symptoms (Chen, Yu, & Yang, 2008;Hermann & Looney, 2011;Iyer et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Better QOL among patients with advanced NSCLC under chemotherapy has been consistently associated with younger age (Henoch, Bergman, Gustafsson, Gaston-Johansson, & Danielson, 2007;Liu et al, 2009); better economic status (Liu et al, 2009;Pan, Xu, Wang, & Zhu, 2011); being employed (Hermann & Looney, 2011); stronger social support (Liang, Jiang, & Li, 2007;Luszczynska, Pawlowska, Cieslak, Knoll, & Scholz, 2013); better performance status (Henoch et al, 2007;Hermann & Looney, 2011;Iyer, Taylor-Stokes, & Roughley, 2013); better treatment response to chemotherapy (Liu et al, 2009;Zhan, 2008); less frequent, severe, and distressing physical symptoms (Hermann & Looney, 2011); and less anxiety and depressive symptoms (Chen, Yu, & Yang, 2008;Hermann & Looney, 2011;Iyer et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 98%
“…El apoyo social, de acuerdo con la literatura previa (26,27) , se asocia con los niveles de ansiedad y depresión, aunque no alcanza la significación en los modelos multivariados.…”
Section: Discussionunclassified
“…El apoyo social es una variable determinante en la adaptación al cáncer (26,27) y por ello se hace necesario controlar su efecto. Dicha variable se ha evaluado mediante el cuestionario MOS de apoyo social (28) (MOS Social Support Survey; MOS-SSS).…”
Section: (Hads)unclassified
“…All of these could have direct and/or indirect effects on survival. Empirically, Luszczynska, et al (Luszczynska et al 2012) found that patients with perceived/received family support had improved psychological and physical quality of life. Stressrelated psychosocial factors have been shown to have a deleterious effect on survival in patients with lung cancer (Chida et al 2008).…”
Section: Discussionmentioning
confidence: 99%